2011
DOI: 10.1007/s11293-011-9275-1
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Attendance in the Quebec Major Junior Hockey League: Role of Winning, Scoring, and Fighting

Abstract: Attendance, Sports, Hockey, Demand, Violence,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 6 publications
2
9
0
Order By: Relevance
“…Results revealed that weekend games, special promotions, division opponents, and night games (after 5:00 p.m. local time) significantly influenced ticket sales for this particular team. Our results confirmed previous research in the NHL and other sport leagues who found that weekend games increased attendance (Cebula et al, 2009;DeSchriver, 2007;Jones et al, 1993, Leeds & Sakata, 2012Lemke et al;Paul, 2003;Paul & Weinbach, 2011). Based on Equation 5 predictions, weekend games would have the greatest positive influence on ticket sales with an estimated 2,993 more tickets sold compared with weekday games.…”
Section: Ticket Salessupporting
confidence: 88%
See 3 more Smart Citations
“…Results revealed that weekend games, special promotions, division opponents, and night games (after 5:00 p.m. local time) significantly influenced ticket sales for this particular team. Our results confirmed previous research in the NHL and other sport leagues who found that weekend games increased attendance (Cebula et al, 2009;DeSchriver, 2007;Jones et al, 1993, Leeds & Sakata, 2012Lemke et al;Paul, 2003;Paul & Weinbach, 2011). Based on Equation 5 predictions, weekend games would have the greatest positive influence on ticket sales with an estimated 2,993 more tickets sold compared with weekday games.…”
Section: Ticket Salessupporting
confidence: 88%
“…This study also analyzed economic models based on spending alone so took a predominantly sports economics perspective in the analysis. While this is an appropriate method for sports economic studies (e.g., Lemke et al, 2010;Paul, 2003, Paul & Weinbach, 2011, Welki & Zlatoper, 1999 other sport fan studies have used behaviorist models to examine fan preferences, attitudes, and sociodemographic variables that might influence sport consumption (e.g., Kwon & Armstrong, 2002;Kwon & Trail, 2003;Zhang, 1998). As such, this study is limited to making conclusions about spending and cannot be extrapolated to fan specific behaviors such as preferences, attitudes, and motivations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Physical play (using penalty minutes as a proxy) was not found to significantly impact attendance in the SM-Liiga in Finland . Fighting was not shown to have a statistically significant impact on attendance in junior hockey in the Quebec Major Junior Hockey League (Paul and Weinbach 2011).…”
Section: Literature Reviewmentioning
confidence: 74%